2023
DOI: 10.1007/s10916-023-01912-9
|View full text |Cite
|
Sign up to set email alerts
|

Operating Room Performance Optimization Metrics: a Systematic Review

Abstract: Literature proposes numerous initiatives for optimization of the Operating Room (OR). Despite multiple suggested strategies for the optimization of workflow on the OR, its patients and (medical) staff, no uniform description of ‘optimization’ has been adopted. This makes it difficult to evaluate the proposed optimization strategies. In particular, the metrics used to quantify OR performance are diverse so that assessing the impact of suggested approaches is complex or even impossible. To secure a higher implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Again, performance frontiers can be used in comparative analyses of multiple institutions in operating room management. Although a wide variety of metrics contributing to operating room performance may exist, a targeted approach in which relevant metrics are adjusted for study followed by evaluation of impact on the breadth of metrics for operating room performance; performance frontiers are perfectly suited for this manner of multi-objective data visualization [20]. Further, different perioperative services can understand the limitations to their own operations, and perhaps, consider redesigning them rather than aiming to meet the minimal standard of an OR management metric.…”
Section: Discussionmentioning
confidence: 99%
“…Again, performance frontiers can be used in comparative analyses of multiple institutions in operating room management. Although a wide variety of metrics contributing to operating room performance may exist, a targeted approach in which relevant metrics are adjusted for study followed by evaluation of impact on the breadth of metrics for operating room performance; performance frontiers are perfectly suited for this manner of multi-objective data visualization [20]. Further, different perioperative services can understand the limitations to their own operations, and perhaps, consider redesigning them rather than aiming to meet the minimal standard of an OR management metric.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 39 studies, Fong et al 8 demonstrated that most studies studied time or money as their metric for efficiency. Schouten et al 27 performed a systematic review and identified that currently no studies account for interactions between metrics of quality and efficiency. Further studies are needed to identify the optimal calculation of metrics that accurately reflect OR efficiency and quality to ensure value to both the patients and institutions.…”
Section: Administrative and Management Considerationsmentioning
confidence: 99%
“…Perioperative and organizational leaders focus on maximizing OR efficiency, a process that likely equates time (eg, delays, on-time starts, between-procedure turnover) with cost. 20 This focus results in a culture that rewards personnel for efficiency and prioritization of practical, patient-related tasks. 21 Nurses do not always prioritize documentation in the same manner as other patient safety concerns (eg, time out, retained surgical item) and key performance metrics.…”
Section: Causes Of Inadequate Documentationmentioning
confidence: 99%
“…Perioperative and organizational leaders focus on maximizing OR efficiency, a process that likely equates time (eg, delays, on‐time starts, between‐procedure turnover) with cost 20 . This focus results in a culture that rewards personnel for efficiency and prioritization of practical, patient‐related tasks 21 .…”
Section: Causes Of Inadequate Documentationmentioning
confidence: 99%